The potential of Curcuma longa L. bioactive compounds as RSK inhibitors for the treatment of prostate cancer: in silico study - Olusola Olalekan Elekofehinti; Foluso Adeola Taiwo; Moses Orimoloye Akinjiyan; Ifeoluwa Rachael Adetoyi; Folasade Oluwatobiloba Ayodeji; Adedotun Olayemi Oluwatuyi; Oluwapelumi Nifesimi Akintoye; Idayat Oyinkansola Kehinde; Bolanle Esther Adedapo; Opeyemi Iwaloye (African Journal of Urology)
Abstract Background The second most seen malignancy occurrence among males is prostate cancer. The p90 ribosomal s6 kinase (RSK) has attracted increased attention due to its overexpression in cancer cells, especially prostate cancer cells. Significant progress has been made recently to develop RSK inhibitors to treat prostate cancer, but these efforts have shown limited success. Methods Molecular docking and other computational analysis procedures using the Schrodinger suite were used to predict in silico the ability of bioactive compounds from turmeric (Curcuma longa) to bind effectively to RSK as potent inhibitors. Forty-three (43) selected compounds from turmeric were screened against RSK. After the molecular and induced-fit docking, the hit compounds were later subjected to ADMET, MMGBSA, and QSAR analyses using the Schrödinger suite. Results Five bioactive compounds may be possible lead drugs for the treatment of prostate cancer because they have the lowest binding energies, ranging from − 9.0 kcal/mol to − 11.00 kcal/mol, and have better pharmacokinetic qualities than the standard drugs docetaxel, enzalutamide, and abiraterone. The ligand and receptor had induced fit scores of − 8.511, − 6.977, − 8.671, − 9.548, and − 8.287 for 3-O-caffeoylquinic acid, 8-hydroxyl-ar-turmeron, bisdemethoxycurcumin, Curcumin II, and demethoxycurcumin, respectively. These hit compounds after ADMET prediction do not violate Lipinski's rule of five. Conclusion The work suggested that turmeric phytocompounds are effective RSK inhibitors for prostate cancer treatment. Further in vivo and in vitro investigations can confirm these findings.